随伴症状を伴ったいわゆるがく関節症の１例 - INUI Akira; HIRA Kazuhiko; MIYAMOTO Kazuya; TAKANO Jun (Japanese Journal of National Medical Services, 1983)
A case of arthrosis of the jaw joint is presented. The patient was a slender, nervous woman of 42 years old. In 1967 and the subsequent years she underwent extraction of teeth 7, 7, 6 and 6 without any prosthetic treatment. It was in 1975 that she had a denture put in. In 1978 she developed dull pain with languor in the left ascending branch. In 1979 the denture was replaced with a new one. This resulted in aggravation of the pain and the development of the protruding sensation of the left mandibular angle and cheek. She visited orthopedic surgeons and otorhinologists, but with no symptomatic improvement. The area of pain was extended to the left maxillary tuberosity and the occipital region as well, together with the protruding sensation of the maxillary front teeth and the mandibular anterior teeth. In addition, there was severe stiffness of the right shoulder, causing her to consult dentists one after another. In Feb. 1980 she developed malocclusion with linguoversion of the mandibular anterior teeth.In Oct. 1980, because of this unbearable pain she visited the outpatient clinic of a dental college. About that time she had the right shoulder sunken with pain developing in the back. No symptomatic improvement was obtained with 12 attempts at occlusal equilibration made by means of the bite raising plate followed by acupuncture anesthesia.Then she was referred to our clinic because of convenience for ambulatory treatment.The chief complaints at the time of the first examination was pain in the right jaw joint during opening of the mouth with tenderness in the retroauricular and buccal regions homolaterally and a sensation of heaviness in the right shoulder, which prevented her from doing household duties satisfactorily. Physical examination revealed that the maximum opening of the mouth was 4.1 cm with transposition to the left of the middle of the mandible by about 0.5 cm and slight protrusion of the right mandible. There was a denture of 876 678 replacing the missing teeth. The teeth 765 were metal-crowned and extruded downward compared to the corresponding teeth on the left. The tooth 7 suffered bucco-version during occlusion. The Yatabe-Guilford personality test revealed a personality of AC type with the desire to lead others and emotional instability. A test for rheumatoid factor was negative. X-ray examination by tomography of the jaw joints during opening and closure of the mouth and frontal view revealed abnormal levels of the left glenoid fossa and condyle head. There was a marked right-left difference in the angle of condyle path as determined by the check bite technique.Therapeutically the occlusal curvature and dentition of the upper jaw were adjusted by modifying the metal crowns of 765. Occlusal equilibration of the mandible was achieved by repair of the denture. The results obtained were satisfactory. 左側顎関節に開口時, 運動制約が見られ, これに反し右側顆頭の開口運動量が大きく, 左右顎運動の不調和を来し, 自覚症状として, 右側顎関節の開口時痛, 右側咬筋浅部前縁及び顎二腹筋後腹部の鈍痛, 右後頭部痛及び同側の肩から背にかけての「こり」, 右肩下りなどを訴え, 家事に専心出来なくなり日常生活に支障を来した年令41才の主婦に対し治療を試み, 咬合彎曲の改善と義歯の改修を行つて, 咬合調整し, 良好な結果が得られたので, その発症の経過, 診断の根拠, 治療などについて検討し, 1例報告する.